Tinjauan Yuridis terhadap Perceraian Menurut Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan Sebagaimana diubah dengan Undang-Undang Nomor 16 Tahun 2019 dan Norma Agama Kristen Protestan - William Ricky Ananta; Khotbatul Laila (Bhirawa Law Journal, 2021)
The divorce rate in Indonesia is getting higher. come from all classes of Indonesian citizens, both high and low social status, and from different religious backgrounds. In Law Number 1 of 1974 concerning Marriage, the aim is to complicate Divorce, but it also regulates divorce. Teachings on the norms of Protestant Christianity also prohibit Divorce which is an act that is hated by the divine Jesus. The church as an institution that regulates Protestant Christians does not allow divorce decisions made by its congregation. Therefore here the author raises the issue of how the juridical review of Divorce according to the Marriage Act and the christian norms of Protestants and the legal consequences for protestant Christians. This research is normative legal research using legislation approach and comparison approach, therefore this research uses primary, secondary, and tertiary legal materials.Based on the research results, the authors obtained answers to existing problems. Termination of Marriage due to Divorce based on the norms of Protestant Christianity for adherents is legal according to the Legislation, however the church as an institution that regulates its people there is still no certainty regarding Divorce. Protestant churches only assist congregations who want to divorce but do not prohibit them because divorce is a civil right of all Indonesian citizens, but the church is still responsible for its congregation who commits divorce. The legal consequences of divorce are the breaking up of the husband and wife relationship, the consequences for the child, and the consequences for joint property. According to the norms of Protestant Christianity, the result of Divorce is sin.